2017
DOI: 10.1177/0267658317691322
|View full text |Cite
|
Sign up to set email alerts
|

The role of morphological complexity in predicting the learnability of an additional language: The case of La (additional language) Dutch

Abstract: Applied linguistics may benefit from a morphological complexity measure to get a better grip on language learning problems and to better understand what kind of typological differences between languages are more important than others in facilitating or impeding adult learning of an additional language. Using speaking proficiency scores of 9,000 adult learners of Dutch as an additional language, we reproduced the findings of the Schepens et al. (2013a) study, using a reduced morphological complexity measure. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The results of the current study support previous findings showing that increased morphological complexity of L2, as compared with L1, results in lower L2 learnability (Schepens et al, 2013a; van der Slik, Hout, & Schepens, 2017). Specifically, the findings may be related to the complexity and to the heavily inflected structure of the Slavic languages, in comparison to English.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the current study support previous findings showing that increased morphological complexity of L2, as compared with L1, results in lower L2 learnability (Schepens et al, 2013a; van der Slik, Hout, & Schepens, 2017). Specifically, the findings may be related to the complexity and to the heavily inflected structure of the Slavic languages, in comparison to English.…”
Section: Discussionsupporting
confidence: 91%
“…This study examined the impact of the morphological complexity of their L1 and L2 on their speaking proficiency scores in Dutch. It was found that adult language learners whose first language (L1) had a less complex morphological feature configuration than Dutch had greater difficulty in acquiring Dutch the less complex their L1 was in relation to Dutch (van der Slik, Hout, & Schepens, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…), and it should be verified whether the measures could be used to gauge proficiency and trace language development in other foreign languages (see Pallotti and Brezina, 2019, De Clercq and Housen, 2019). This is a particularly promising avenue for research as it will make it possible to appraise the role of complexification vis-à-vis crosslinguistic influence in foreign language development (see Ehret and Szmrecsanyi, 2019; van der Slik et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also recognized that interlanguage complexity can, and should, be studied in other domains of the language system, such as phonology, lexis or morphology (e.g. Bulté and Housen, 2012; De Clercq and Housen, 2019; Housen et al, 2019; Pallotti and Brezina, 2019; van der Slik et al, 2019; Wolfe-Quintero et al, 1998). However, no systematic attempt has been made to date to theorize and operationalize linguistic complexity at the level of word combinations.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, when repeating Polish sentences in the SRep task, which involves accessing the mental representation of a given structure, the knowledge of English syntactic templates possibly interfered with the knowledge of Polish syntax, leading to errors in the production of syntactically complex Polish sentences. Another possible explanation is that the early acquisition of English, a language less morphosyntactically complex than Polish, “desensitized” children to the complexity of Polish inflection ( van der Slik et al, 2017 ). However, at this point the above interpretations of the negative effect of L2 exposure on the scores in L1 SRep task are only speculative.…”
Section: Discussionmentioning
confidence: 99%